Coulomb Excitation of 68Ni at "safe" energies - Bree, N.; Stefanescu, I.; Cederkäll, Joakim (Physical Review C (Nuclear Physics), 2008)
The B(E2;0+2+) value in 68Ni has been measured using Coulomb excitation at safe energies. The 68Ni radioactive beam was postaccelerated at the CERN on-line isotope mass separator (ISOLDE) facility to 2.9 MeV/u and directed to a 108Pd target. The emitted rays were detected by the MINIBALL detector array. Not only directly registered but also indirectly deduced information on the nucleus emitting the ray was used to perform the Doppler correction, leading to a larger center-of-mass angular range to infer the excitation cross section. The obtained value of 2.8×102e2 fm4 is in good agreement with the value measured at intermediate energy Coulomb excitation, confirming the low 0+2+ transition probability.